Specialty services offered by pharmacists in the community - Anthony P. Morreale; Julie A. Groppi; Heather Ourth (BMC, 2019)
Abstract In a recent IJHPR article, Schwartzberg and colleagues report on clinical and other specialty services offered by pharmacists in the community in Israel and in the international arena. The article covers examples of activities recently introduced due to legislative changes which expanded the pharmacist's scope of practice, along with obstacles that are serving to slow broader expansion and availability of these services. This commentary details the success of clinical pharmacy services being provided by the United States Veterans Health Administration, and offers a framework of elements that support clinical pharmacy practice expansion.